Time-optimal control of parabolic time lag system - Kowalewski, Adam; Krakowiak, Anna (Zielona Góra: Uniwersytet Zielonogórski)
A time-optimal control problem for a distributed parabolic system in which constant time lags appear both in the state equation and in the boundary condition is presented. Some particular properties of the optimal control are discussed.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka